Factors For Determining Dental Anxiety Level in Elementary School Children with Tooth Extraction: A Cross-Sectional Study - Amirah Dini Masula; Ratih Larasati; Siti Fitria Ulfah; Aporn Deenan (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Anxiety in the action of tooth extraction is often caused by the use of sharp objects that are carried out gradually into the oral cavity. Anxiety of dental medical personnel can be the main cause decline dental and oral health. The problem in this study is dental anxiety about tooth extraction in children at SDN Pekarungan Kec. Sukodono, from the results of initial data collection, it was found that 40% had low and moderate anxiety. This study aims to determine the effect of factors for determining dental anxiety in elementary school children with tooth extraction. Methods: The type of research used is analytic cross sectional with purposive sampling technique, the total population is 416 students and the sample obtained is 87 respondents using the cross-sectional formula. Data analysis using chi-square test and ordinal regression analysis. The result of the study there are two factors that influence dental anxiety on tooth extraction using chi-square test, namely gender (p=0.035) and parents education (p=0.001) and there is the most influential factor using logistic regression analysis test, namely parents education ( p=0.001) with an odds ratio value (9.31). In conclusion, most of the respondents experienced moderate anxiety and the influencing factors were gender and parent’s education. The benefit of this research is to provide input for health workers, especially dentists and dental nurses, in providing good dental and oral health care efforts by paying attention to the level of anxiety in pediatric patients who will have their teeth extracted.